Application of International Telecommunication Union Recommendation L.1480 on measuring the greenhouse gas emission effects to a use case for photovoltaic power generation equipment - François Bélorgey; Jérôme Fournier; Nathalie Labidurie Omnes (Environmental Research: Energy)
This article generalizes ITU-T Recommendation L.1480 ‘Enabling the Net Zero transition: Assessing how the use of information and communication technology solutions impact greenhouse gas emissions of other sectors’ ( www.itu.int/rec/T-REC-L.1480-202212-I ) by applying it to an action outside the Information and Communication Technology (ICT) field covered by this ITU-T Recommendation L.1480, namely the use of a photovoltaic solar power plant in Poland, including the transition to scale. The study quantifies this use by accounting all greenhouse gases (GHG) emissions consequences (incl. installation, operation and maintenance) over the duration of the action (i.e. the supply and operation of the photovoltaic panels, inverter and associated services), through the construction of a consequence tree and the effective observation of usage behaviors; it thus avoids pushing potentially negative effects outside the scope of the study, like rebound effects (ex.: increase of 10% in electricity consumption after photovoltaic panels commissioning) or the consequences of the use of financial gains (or losses). Three main innovations are shown: By assessing all GHG emissions consequences and defining the steps for carrying out this assessment, L.1480 methodology covers all effects on a global scale and reflects real changes in GHG emissions. It could thus be applied to assessing the GHG emissions consequences of actions and decisions of various kinds: public policies (like carbon storage), corporate investment or household behavior. Moreover, adding other categories of environmental impact (biodiversity, scarcity of natural resources (metals, water), waste and pollution, radiative effect, etc) would improve the exhaustiveness of environmental effects measurement.